Photodegradation of Rhodamine B over unexcited semiconductor compounds of BiOCl and BiOBr - Chang, Xiaofeng; Gondal, M.A.; Al-Saadi, A.A.; Ali, M.A.; Shen, Hefei; Zhou, Qin; Zhang, Jun; Du, Mengping; Liu, Yousong; Ji, Guangbin (Journal of colloid and interface science, 2012)
[Display omitted] ► Photosensitized degradation of Rodamine B was investigated on BiOX (X=Cl, Br). ► Methylene Blue could not be degraded on BiOX under visible light irradiation. ► The relationship between LOMO of dye molecules and degradation rate was established. This study reported, for the first time systematically, photodegradation of Rhodamine B (RhB) in aqueous solution over BiOCl and BiOBr semiconductors. Under visible light irradiation (λ>400nm, λ>420nm and λ=550±15nm), RhB adsorbed on the surface of BiOCl and BiOBr was photosensitized and decomposed effectively over unexcited BiOCl and BiOBr. The degradation of Methyl Orange (MO) and Methylene Blue (MB) over BiOCl and BiOBr was investigated as well, and the results were compared with RhB photodegradation. It was found that MB molecules having the lowest LUMO could not be degraded by this process. Utilizing the quantum chemical calculation (Gaussian 03 program), the relationship between frontier orbital energy of selected dye molecules and photodegradation rate was established for the first time in this study.